Quality of life of women with breast cancer undergoing chemotherapy - Edianne Sílvia Lustosa Cesar; Inez Sampaio Nery; Államy Danilo Moura e Silva; Juliana Teixeira Nunes; Ana Fátima Carvalho Fernandes (Rev Rene)
Objective: to analyze the quality of life of women with breast cancer undergoing chemotherapy. Methods: a cross-sectional study with 76 women. We used the European Organization for Research and Treatment of Cancer Core Quality of Life Questionnaire-30 and Supplementary Questionnaire Breast Cancer Module. Results: there was a low correlation between socio-demographic and clinical variables with the quality of life domains. The best scores corresponded to women from 49 to 51 years old, married, dark-skinned, better schooling and formal work. The least mentioned symptoms were: Swollen breast (84.2%), Vomiting (81.6%); Shortness of breath (80.3%). Conclusion: general health presented satisfactory average, which suggests a good quality of life according to the European Organization for Research and Treatment of Cancer Core Quality of Life Questionnaire-30. However, the Functional and Symptoms domains, as measured by Supplementary Questionnaire Breast Cancer Module, were negatively influenced by old age and larger cycles of chemotherapy.